Possible relaxation and conduction mechanism in W6+doped SrBi4Ti4O15 ceramic. Issue 5 (1st April 2017) - Nayak, P.; Badapanda, T.; Singh, A.K.; Panigrahi, S.
Abstract: Tungsten (W) doped Strontium Bismuth Titanate ceramics with general formula [SrBi4-2x/3 Ti4−x Wx O15 (x=0.00, 0.02, 0.04, 0.06, 0.08, 0.1)] were prepared via solid-state reaction route. The X-ray diffraction analysis confirmed a single phase system with orthorhombic structure for all the prepared samples. The relaxation and conduction mechanism were studied by using impedance spectroscopy analysis. The shifting of Z"max and M"max peak to the higher frequency side in accordance with temperature for all the sample are found to obey the Arrhenius law, indicates the presence of relaxation process in the material. The complex impedance plots showed that both grain and grain boundary are responsible for the conduction mechanism and the grain and grain boundary resistance decreases with temperature showing NTCR behaviour in all the compositions. The kinetic analysis of frequency dependence ac conductivity have been discussed in terms of polaron mechanism and the dc conductivity shows a thermally activated process. We have observed that the charge carrier hopping and doubly ionized oxygen vacancy (Vₒ) are mainly responsible for the conduction mechanism in the systems.